Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Meier, Torsten

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Einsatzmöglichkeiten von digitalen Medien im Physikunterricht - eine Übersicht - Weiler, David; Burde , Jan-Philipp; Große-Heilmann, Rike Isabel; Riese, Josef; Schubatzky, Thomas (Plus Lucis)

Electric-field-induced second harmonic generation in silicon dioxide - Widhalm, Alex; Golla, Christian; Weber, Nils; Mackwitz, Peter; Zrenner, Artur; Meier, Cedrik (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Fachliche und überfachliche Herausforderungen in der Studieneingangsphase Physik - Bauer, Anna; Woitkowski, David; Reuter, Dirk; Reinhold, Peter (Hochschullehre erforschen.)
Die Studieneingangsphase Physik stellt für die Studienanfänger Innen einen komplexen Lernprozess mit vielfältigen Anforderungen auf fachlicher, Metakognitions- und Sozialisations-Ebene dar, der ihre akademische Identitätsbildung beeinflusst und prägt. Ziel des Projektes Paderborner Studieneingangsphase Physik (PSΦ) ist die evidenzbasierte Gestaltung eines strukturierten Studieneinstiegs und einer in sich kohärent abgestimmten Studieneingangsphase „aus einem Guss“. Die Implementation eines neuen Übungsformats (Präsenzübungen) in den Fachvorlesungen sowie die Unterstützung der Studierenden im Bereich des selbstregulierten Lernens zeigen positive Effekte in einer erhöhten Teilnahmequote sowie Zufriedenheit der Studierenden mit der Veranstaltung, in einem aktiveren Arbeitsverhalten sowie einer höheren Bestehensquote der Klausur. Ein messbar größerer Fachwissenserwerb konnte nicht nachgewiesen werden. Auf Basis der Evidenzen konnten Stellschrauben für die Weiterentwicklung sowie für die Unterstützung der Lehrenden abgeleitet werden. In dem Beitrag werden die Gelingensbedingungen und Strukturen für eine wirksame Zusammenarbeit von Fachdidaktik und Fachwissenschaft am Beispiel der Überarbeitung der Studieneingangsphase im Rahmen einer community of practice sowie der Wirksamkeit der Implementierung diskutiert.

A Versatile Metasurface Enabling Superwettability for Self‐Cleaning and Dynamic Color Response - Lu, Jinlong; Sain, Basudeb; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Zentgraf, Thomas (Advanced Optical Materials)
Metasurfaces provide applications for a variety of flat elements and devices due to the ability to modulate light with subwavelength structures. The working principle meanwhile gives rise to the crucial problem and challenge to protect the metasurface from dust or clean the unavoidable contaminants during daily usage. Here, taking advantage of the intelligent bioinspired surfaces which exhibit self-cleaning properties, a versatile dielectric metasurface benefiting from the obtained superhydrophilic or quasi-superhydrophobic states is shown. The design is realized by embedding the metasurface inside a large area of wettability supporting structures, which is highly efficient in fabrication, and achieves both optical and wettability functionality at the same time. The superhydrophilic state enables an enhanced optical response with water, while the quasi-superhydrophobic state imparts the fragile antennas an ability to self-clean dust contamination. Furthermore, the metasurface can be easily switched and repeated between these two wettability or functional states by appropriate treatments in a repeatable way, without degrading the optical performance. The proposed design strategy will bring new opportunities to smart metasurfaces with improved optical performance, versatility, and physical stability.

Second Harmonic Optical Circular Dichroism of Plasmonic Chiral Helicoid-III Nanoparticles - Spreyer, Florian; Mun, Jungho; Kim, Hyeohn; Kim, Ryeong Myeong; Nam, Ki Tae; Rho, Junsuk; Zentgraf, Thomas (ACS Photonics)
While plasmonic particles can provide optical resonances in a wide spectral range from the lower visible up to the near-infrared, often, symmetry effects are utilized to obtain particular optical responses. By breaking certain spatial symmetries, chiral structures arise and provide robust chiroptical responses to these plasmonic resonances. Here, we observe strong chiroptical responses in the linear and nonlinear optical regime for chiral L-handed helicoid-III nanoparticles and quantify them by means of an asymmetric factor, the so-called g-factor. We calculate the linear optical g-factors for two distinct chiroptical resonances to −0.12 and –0.43 and the nonlinear optical g-factors to −1.45 and −1.63. The results demonstrate that the chirality of the helicoid-III nanoparticles is strongly enhanced in the nonlinear regime.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, D.; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, K. D.; Reuter, D.; Schumacher, S.; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Spin-Orbit Interaction of Light Enabled by Negative Coupling in High-Quality-Factor Optical Metasurfaces - Gao, Wenlong; Sain, Basudeb; Zentgraf, Thomas (Physical Review Applied)
Keywords: General Physics and Astronomy

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Asymmetric parametric generation of images with nonlinear dielectric metasurfaces - Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Dong, Zhaogang; Yang, Joel; Zentgraf, Thomas; Kivshar, Yuri (Nature Photonics)
Subwavelength dielectric resonators assembled into metasurfaces have become a versatile tool for miniaturizing optical components approaching the nanoscale. An important class of metasurface functionalities is associated with asymmetry in both the generation and transmission of light with respect to reversals of the positions of emitters and receivers. The nonlinear light–matter interaction in metasurfaces offers a promising pathway towards miniaturization of the asymmetric control of light. Here we demonstrate asymmetric parametric generation of light in nonlinear metasurfaces. We assemble dissimilar nonlinear dielectric resonators into translucent metasurfaces that produce images in the visible spectral range on being illuminated by infrared radiation. By design, the metasurfaces produce different and completely independent images for the reversed direction of illumination, that is, when the positions of the infrared emitter and the visible light receiver are exchanged. Nonlinearity-enabled asymmetric control of light by subwavelength resonators paves the way towards novel nanophotonic components via dense integration of large quantities of nonlinear resonators into compact metasurface designs.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Potenziale und Grenzen von Unterstützungsmaßnahmen zum wissenschaftlichen Schreiben im Paderborner Physik Praktikum 3P - Bauer, Anna Brigitte; Lahme, Simon Zacharias; Sacher, Marc (PhyDid A - Physik und Didaktik in Schule und Hochschule)
Eines der Lernziele des Physikstudiums stellt der Erwerb literaler Fähigkeiten für das Verfassen wissenschaftlicher Arbeiten dar. Die Student:innen werden allerdings im Rahmen ihres Studiums bisher kaum systematisch beim Erwerb dieser Fähigkeiten unterstützt. Eine Übungsgelegenheit für das Verfassen von Texten nach wissenschaftlichem Vorbild stellt das Laborpraktikum dar, in dem die Student:innen zu den absolvierten Experimenten Laborberichte verfassen. Im Paderborner Physik Praktikum 3P wurden in den letzten Jahren vier unterschiedliche Unterstützungsangebote für das Erlernen des wissenschaftlichen Schreibens entwickelt und mittels Zufriedenheitswerten evaluiert. In dem Beitrag werden die vier Angebote auf inhaltlicher Ebene hinsichtlich der Lernwirksamkeit mittels einer schriftproduktbasierten Evaluation analysiert. Durch die vergleichende Analyse können Potenziale und Grenzen der Angebote diskutiert und Implikationen für die Gestaltung von Unterstützungsangeboten zum Erlernen des wissenschaftlichen Schreibens in der Physik abgeleitet werden.
Keywords: Laborpraktikum; Schreiben

Design and investigation of a metalens for efficiency enhancement of laser-waveguide coupling in a limited space system - laeim, Huddad; Schlickriede, Christian; Chaisakul, Papichaya; Chattham, Nattaporn; Panitchakan, Hathai; Siangchaew, Krisda; Zentgraf, Thomas; Pattanaporhratana, Apichart (Metamaterials, Metadevices, and Metasystems 2022)

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Experimental verification of the acoustic geometric phase - Liu, Bingyi; Zhou, Zhiling; Wang, Yongtian; Zentgraf, Thomas; Li, Yong; Huang, Lingling (Applied Physics Letters)
Optical geometric phase encoded by in-plane spatial orientation of microstructures has promoted the rapid development of numerous functional meta-devices. However, pushing the concept of the geometric phase toward the acoustic community still faces challenges. In this work, we utilize two acoustic nonlocal metagratings that could support a direct conversion between an acoustic plane wave and a designated vortex mode to obtain the acoustic geometric phase, in which an orbital angular momentum conversion process plays a vital role. In addition, we realize the acoustic geometric phases of different orders by merely varying the orientation angle of the acoustic nonlocal metagratings. Intriguingly, according to our developed theory, we reveal that the reflective acoustic geometric phase, which is twice the transmissive one, can be readily realized by transferring the transmitted configuration to a reflected one. Both the theoretical study and experimental measurements verify the announced transmissive and reflective acoustic geometric phases. Moreover, the reconfigurability and continuous phase modulation that covers the 2π range shown by the acoustic geometric phases provide us with the alternatives in advanced acoustic wavefront control.
Keywords: Physics and Astronomy (miscellaneous)

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Nutzungsverhalten von Lehrkräften bei der Implementierung einer physikdidaktisch innovativen Unterrichtskonzeption - Breuer, Judith; Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Eine zentrale Aufgabe fachdidaktischer Forschung stellt die Verbesserung schulischen Unterrichts dar. Die freie Bereitstellung wirksamer Unterrichtskonzeptionen zur Unterstützung des Selbststudiums von Lehrkräften bildet eine Strategie für eine flächendeckende Implementierung fachdidaktischer Innovationen. Allerdings etablieren sich zahlreiche, empirisch erfolgreich evaluierte Unterrichtskonzeptionen nicht nachhaltig an Schulen. Daher untersucht das vorliegende Forschungsvorhaben den Implementationsprozess solcher Materialien unter authentischen Bedingungen. Dazu wurde kriteriengeleitet eine evidenzbasierte, fachdidaktisch innovative Unterrichtskonzeption ausgewählt: das Münchener Unterrichtskonzept zur Quantenmechanik (MILQ). Diese wurde den teilnehmenden Lehrkräften fakultativ zur Verfügung gestellt. Mittels Fallstudien wurde die Implementierung von MILQ von elf Lehrkräften durch halbstandardisierte Interviews zu Beginn und am Ende einer Unterrichtsreihe zur Quantenmechanik sowie zwei Unterrichtsbeobachtungen mit je einem anschließenden stimulated recall explorativ erfasst. Die Probanden setzten sich überwiegend heuristisch mit MILQ auseinander und implementierten vor allem Elemente auf Sichtstrukturebene im Unterricht, die konform zu ihren bisherigen Vorstellungen waren. Dadurch wurde das fachdidaktische Innovationspotential nicht ausgeschöpft. Bezeichnend ist, dass der empirische Wirksamkeitsnachweis von MILQ für die Beurteilung der Lehrkräfte nicht relevant war, was aus theoretischer Sicht bislang als ein zentrales Argument der Bereitstellungsstrategie zur Implementierung fachdidaktischer Innovation angenommen wurde.
Keywords: General Medicine

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

How to Teach a Teacher: Challenges and Opportunities in Physics Teacher Education in Germany and the USA - Van Dusen, Ben; Vogelsang, Christoph; Taylor, Joseph; Cauet, Eva (Physics Education)

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Wie können Erklärvideos zum Erwerb physikalischen Konzeptwissens beitragen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Information extraction in photon-counting experiments - Schapeler, Timon; Bartley, Tim (Physical Review A)

Laser-lithographically written micron-wide superconducting nanowire single-photon detectors - Protte, Maximilian; Verma, Varun B; Höpker, Jan Philipp; Mirin, Richard P; Woo Nam, Sae; Bartley, Tim (Superconductor Science and Technology)
Abstract We demonstrate the fabrication of micron-wide tungsten silicide superconducting nanowire single-photon detectors on a silicon substrate using laser lithography. We show saturated internal detection efficiencies with wire widths ranging from 0.59 µ m to 1.43 µ m under illumination at 1550 nm. We demonstrate both straight wires, as well as meandered structures. Single-photon sensitivity is shown in devices up to 4 mm in length. Laser-lithographically written devices allow for fast and easy structuring of large areas while maintaining a saturated internal efficiency for wire widths around 1 µ m.
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Metals and Alloys; Condensed Matter Physics; Ceramics and Composites

Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Professionalitätsentwicklung angehender Lehrkräfte - Kirsch, Alexander

Kooperatives Unterrichten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven naturwissenschaftlichen Sachunterricht - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Messung von Unterrichtsplanungskompetenz im Fach Sachunterricht: Empirische Befunde zur Kompetenzentwicklung angehender Grundschullehrkräfte auf Grundlage einer mehrdimensionalen Kompetenzstruktur - Kirsch, Alexander (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im vorliegenden Beitrag werden nach ausführlicher theoretischer Diskussion des Kompetenzbegriffs und der Definition von Kompetenz als Können ein Modell sachunterrichtlicher Planungskompetenz sowie ein daran anschließendes Messinstrument vorgestellt. Im Hinblick auf den Einsatz dieses Instrumentes im Rahmen einer Evaluation des nordrhein-westfälischen Praxissemesters stellen sich Fragen nach der psychometrischen Struktur der Testauswertung. Da das Instrument sowohl zur Testung von Sachunterrichtsstudierenden mit dem Lehramtsprofil ‚Grundschule‘ als auch von Sachunterrichtsstudierenden mit sonderpädagogischem Schwerpunkt eingesetzt werden soll, ist zu zeigen, dass die Testergebnisse nicht durch den gewählten Studiengang beeinflusst werden. Im Beitrag werden Rohdaten aus einer Studie an der Universität Paderborn ( n = 121) genutzt, um eine fünfdimensionale Modellstruktur gegen eine eindimensionale zu testen und empirisch gestützte Argumente für eine mehrdimensionale Skalierung zu generieren. Durch Differential-Item-Functioning-Analysen wird geprüft, ob die Itemschwierigkeiten mit dem Merkmal ‚Studiengang‘ interagieren, sodass sie sich trotz gleicher Kompetenzausprägung für Untersuchungsteilnehmende beider Studierendengruppen signifikant unterscheiden und zu einer diagnostischen Verzerrung führen würden. Abschließend wird der beispielhafte Einsatz des Instrumentes im Rahmen einer Wirksamkeitsanalyse in Bezug die Effektivität des nordrhein-westfälischen Praxissemesters an der Universität Paderborn ( n = 26) dargelegt. Aus den differenzierten Ergebnissen werden unter anderem erste Hinweise auf Defizite in der Lehrerinnen- und Lehrerausbildung abgeleitet.
Keywords: Education

Effects of Teacher Feedback on Primary School Students’ Self-Efficacy Beliefs and their Interest in Science Lessons. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Ausbildung in der zweiten Phase der Lehrerbildung. - Tenberge, Claudia (Professionalisierung von Grundschullehrkräften.)

Holz erleben. Technik verstehen. - Möller, Kornelia; Eikmeyer, Birgit; Tenberge, Claudia; Wilke, Torben; Zolg, Monika

Pre-Service Teachers’ Collaborative Lesson Planning and their Self-Concepts in Inclusive Education. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Schöpfen, gautschen, trocknen. Wassereinsatz in der Papierherstellung. - Tenberge, Claudia (Grundschule Sachunterricht.)

Theorien und Konzeptionen inklusiven Sachunterrichts - Schröer, Franz; Tenberge, Claudia (Inklusive (Fach-)Didaktik in der Primarstufe - Ein Lehrbuch)
Das Lehrbuch umfasst Beiträge zur Einführung in den Inklusionsdiskurs, zu Modellen der Allgemeinen Didaktik und der inklusiven Didaktik, zur praxeologischen Unterrichtsforschung, zum Mathematik-, Deutsch-, Sach-, Kunst-, Religions-, Englisch- und Sportunterricht sowie Kommentare zum Zusammenhang der aufgeführten Themenbereiche.

Future Primary Teacher Education: Computational Thinking and STEAM. - Lenke, Michael; Tenberge, Claudia

Über die Dächer der Welt. - Tenberge, Claudia (Grundschule Sachunterricht.)

Technisches Lernen im Sachunterricht inklusiv gestalten - Fördert ein inklusionssensibles Seminar in der universitären Lehrerbildung das Interesse und die Selbstwirksamkeitserwartung von Bachelorstudierenden? - Schröer, Franz; Tenberge, Claudia (widerstreit Sachunterricht - Auf die Lehrkraft kommt es an? Professionalisierung von Lehrkräften für inklusiven Sachunterricht)

Entwicklung und Evaluation eines Fortbildungskonzepts im Kontext der technischen Bildung an Grundschulen am Beispiel von Lernrobotern - Janicki, Nicole (Technik: Verstehen wir, was wir nutzen!? - Tagungsband zur 23. Jahrestagung der Deutschen Gesellschaft für Technische Bildung in Mannheim vom 24.-25. September 2021.)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots